2012
DOI: 10.1016/j.nuclphysb.2012.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy induced scaling of the correlation length for periodic models

Abstract: The broken symmetric phase of scalar models exhibits an infrared fixed point which is induced by the degenerate effective potential. The definition of the correlation length in the infrared regime enables us to determine the type of the phase transition in the model. It is shown that the massive sine-Gordon model exhibits a continuous, while the layered sine-Gordon model has an infinite order Kosterlitz-Thouless type phase transition.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…In d = 4, the WF fixed point (green dot in figure 1) merges to the Gaussian one (black). The IR fixed point (red) appears in any dimensions and is related to the convexity of the potential [47][48][49][50][51][52].…”
Section: Jhep05(2015)141mentioning
confidence: 99%
“…In d = 4, the WF fixed point (green dot in figure 1) merges to the Gaussian one (black). The IR fixed point (red) appears in any dimensions and is related to the convexity of the potential [47][48][49][50][51][52].…”
Section: Jhep05(2015)141mentioning
confidence: 99%
“…This is the case in QEG, too [21][22][23]. We calculated the exponent ν by the dynamically induced correlation [23,32,33] around the IR fixed point. We obtained that the exponent ν around the IR fixed point equals the one calculated around the GFP and it is ν = 1/2.…”
Section: Infrared Criticalitymentioning
confidence: 99%
“…In the IR limit, the MSG model shows a second order phase transition. There, we got ν ¼ 1=2 [30] for the exponent of the correlation length in Eq. (13).…”
Section: The Sine-gordon Model With a Relevant Couplingmentioning
confidence: 99%
“…It was shown that there exists an IR fixed point [23,24], which appears in the low energy-scaling regime of the broken symmetric phase. There are further models where the IR fixed point was identified successfully [24,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation